2019
DOI: 10.1155/2019/5476372
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Contributing Factors of Excessive Daytime Sleepiness in Chinese Obstructive Sleep Apnea Patients: The Role of Comorbid Symptoms and Polysomnographic Variables

Abstract: Background. The occurrence and severity of excessive daytime sleepiness (EDS) vary considerably among obstructive sleep apnea (OSA) patients. This study was designed to investigate the characteristics of EDS and identify its contributing factors in OSA patients. Methods. This was a cross-sectional study from a tertiary medical center in China. A total of 874 consecutive patients with newly diagnosed OSA were included. Subjective daytime sleepiness was assessed with the Epworth Sleepiness Scale (ESS). The subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
0
21
1
Order By: Relevance
“…Chinese OSA patients have their particularities. For example, compared with their counterparts in western countries, Chinese OSA patients have a lower body mass index (BMI), which we have shown in two previous studies 16,17 . This not only represents the characteristics of Chinese patients, but also to some extent, the characteristics of relatively lean OSA patients in East Asia.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Chinese OSA patients have their particularities. For example, compared with their counterparts in western countries, Chinese OSA patients have a lower body mass index (BMI), which we have shown in two previous studies 16,17 . This not only represents the characteristics of Chinese patients, but also to some extent, the characteristics of relatively lean OSA patients in East Asia.…”
Section: Introductionmentioning
confidence: 58%
“…In OSA patients, daytime sleepiness may be related to AHI, sleep fragmentation, and nocturnal hypoxia 24 . Our previous study has shown that in addition to AHI, changes of sleep architecture, SL, and nocturnal mean oxygen saturation are independent predictors of excessive daytime sleepiness 16 . Therefore, we speculate that the higher ESS score of smoking OSA patients may be related to the combined effects of nicotine, changes in sleep architecture, and nocturnal hypoxia.…”
Section: Discussionmentioning
confidence: 95%
“…It is estimated that EDS is present in about 30% of obese individuals with BMI > 35 kg/m 2 and might be independent from OSA presence 32 . The postulated EDS and obesity relationship could be explained by multiple pathophysiological mechanisms including overactivity of autonomic nervous system, hormonal and metabolic changes and obesity-related medical conditions [33][34][35] . Impact of weight loss on aforementioned pathways could partially clarify beneficial impact of bariatric surgery on EDS.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as fragmented sleep due to respiratory events have previously been related to EDS. [19] EDS is one of the major consequences of OSA. EDS has a greater frequency of traffic accidents due to drivers falling asleep at the wheel.…”
Section: Discussionmentioning
confidence: 99%
“…The AHI was calculated by dividing the total number of apnoea-hypopnea episodes by the number of hours of sleep. Based on AHI, OSA was classified as Mild (<15), moderate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), or severe (>30). [11][12]…”
Section: Study Populationmentioning
confidence: 99%